Secure Dna Data Compression Using Algebraic Curves - Soto-Gomez, J (Institution of Engineering and Technology, 2015)
A system that achieves compression using artificial DNA packaging with the support of two algebraic curves is presented, whereby the Hermitian channel code algorithm introduces gain and safety. Additionally, performance results are presented with a gain of 7 dB against uncoded quadrature phase shift keying and 1 dB against McEliece, for a bit error rate of 10?3. The results of the security levels compared with the McEliece system are also presented. © 2015 The Institution of Engineering and Technology.